Utilization of ultrasonic-assisted extraction for antioxidants isolation from black rice and its impact on the characteristics of chitosan films: Utilization of ultrasonic-assisted extraction for antioxidants isolation from black rice bran and its impact on the characteristics of chitosan films - Duanginta, Kanchaphon; Sokanket, Supaporn; Kanha, Nattapong; Laokuldilok, Thunnop (Food and Applied Bioscience Journal, 2023)
Black rice bran is rich in anthocyanins and phenolic compounds, both renowned for their potent antioxidant properties. The use of ultrasound technology in combination with solvent extraction has the potential to increase the efficiency of extracting antioxidants from black rice bran. This study was conducted to investigate the optimal conditions for the extraction of antioxidants from black rice bran using ultrasonic-assisted extraction. Four key factors were examined: the rice bran-to-solvent ratio (1:13-1:27 w/v), extraction time (16-44 min), power intensity (25-95% amplitude), and pulse duration (1-9 seconds). The rice bran-to-solvent ratio and extraction duration exhibited a significant influence on DPPH radical scavenging activity, whereas power intensity and pulse duration notably impacted the total phenolic content and DPPH radical scavenging activity. The optimal extraction conditions were determined to be a 1:15 ratio of rice bran to solvent, a 20 min extraction duration, 66% amplitude, and a 3-second pulse. Under these conditions, the extraction yielded total phenolic and anthocyanin contents of 12.41 mg/g and 3.88 mg/g, respectively, with a DPPH radical scavenging activity (IC50) of 63.19 mg/g. Chitosan films infused with the black rice bran extract exhibited reduced tensile strength compared to the control. The incorporation of glycerol, known to enhance film flexibility, resulted in increased elongation at break. Interestingly, the addition of the extract did not significantly alter the elongation at break but led to a decrease in L* and b* values and an increase in a* value of the chitosan films. The findings of this study demonstrate the potential for enhancing the extraction efficiency of antioxidative compounds from black rice bran through ultrasound technology, leading to the production of chitosan films incorporating black rice bran anthocyanins potentially to be utilized as a pH-sensitive indicator film